Post Study Design of Wireless Network for the Water Dilemma in the city of Rujban (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Providing water for daily life usage is one of the biggest obstacles facing the growth and development of cities not only in Libya but in many countries of the world. The city of Rujban faces this crisis despite the passage of more than five decades in trying to resolve this issue. We did some deep research and study on the water system operation problem which we divided into three parts: Karthoom Automated Control System (KACS), Idref Automated Control System 1(IACS1), Idref Automated Control System 2 (IACS2) because water is pumped on 3 different stages. The IACS1 consists of two main parts: transmitter/collector tank on one side and receiver / pumps on the other side. The transmitter end consists of a microcontroller, three stage level sensor, two water flow sensors and an RF transmitter. The other end consists of two water pumping pump and an RF receiver. The system will be automated by the use of a microcontroller in which each level of the collector tank will be designed to turn on just one or both pumps of in the case there is certain amount of water, which can be determined by water level sensor, in Karthom collection tank. A crucial part of this coordination is the flow meter which will indicate if the pump is operational or not and detect whether or not there is water leakage, all of which will be demonstrated on an LCD screen. In this paper, we will design a wireless communication network for IACS1.